2010
DOI: 10.1007/s11430-010-4115-8
|View full text |Cite
|
Sign up to set email alerts
|

Particles carried by ascending gas flow at the Tongchanghe copper mine, Guizhou Province, China

Abstract: We collected and analyzed, using transmission electron microscopy, the particles carried by ascending gas flow in soil above the concealed orebody of the Tongchanghe copper mine, Guizhou Province. Particles of native copper, native copper-iron alloy, and native chromium-iron-copper alloy particles in the ascending gas flow were first discovered. Commonly, they were aggregations of relatively small particles. Individual particles within aggregations were subcircular, elliptical, regularly polygonal, or elongate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…Moreover, sulfate aerosols can directly affect the climate (Graf et al, 1998). In our previous work, particles carried by an ascending geogas flow in the soil (Holub et al, 1999(Holub et al, , 2001Cao et al, 2009Cao et al, , 2010bCao et al, , 2011Liu et al, 2011;Wei et al, 2013;Hu et al, 2015) were studied and found to contain sulfur. Further research showed that sulfur-containing particles carried by ascending geogas flows can be transported through the soil layers and into the atmosphere.…”
Section: Introductionmentioning
confidence: 98%
“…Moreover, sulfate aerosols can directly affect the climate (Graf et al, 1998). In our previous work, particles carried by an ascending geogas flow in the soil (Holub et al, 1999(Holub et al, , 2001Cao et al, 2009Cao et al, , 2010bCao et al, , 2011Liu et al, 2011;Wei et al, 2013;Hu et al, 2015) were studied and found to contain sulfur. Further research showed that sulfur-containing particles carried by ascending geogas flows can be transported through the soil layers and into the atmosphere.…”
Section: Introductionmentioning
confidence: 98%
“…Previous studies have also proved that soil overlying ore deposits can present anomalous concentrations of corresponding ore‐forming elements (Levitan et al, ; Sadeghi et al, ). It was also demonstrated that metal‐bearing particles can transfer upwards through ascending gas flow and ground water (Cao et al, , ; Cao, ; Hu et al, ; Li et al, ). Luo et al () has demonstrated that there were many metal‐bearing particles preserved in the soil above the orebodies.…”
Section: Discussionmentioning
confidence: 99%
“…The origins and migration forms of the particles carried by the ascending gas flow are one of the important problems to solve in geogas prospecting, and they play an extremely important role in the application of deposit prospecting (Cao, 2011;Cao et al, 2009Cao et al, , 2010aEtiope and Lombardi, 1996;Malmqvist, 1980, 1982;Zhou et al, 2003). In our studies, the particles carried by the ascending gas flow and the corresponding soil samples were collected and analyzed by TEM technique.…”
Section: Comparison Of Particles Carried By the Ascending Gas Flow Wimentioning
confidence: 99%
“…A comparison of the particles carried by the ascending gas flows from four different deposits (Cao et al, , 2010aWei et al, 2013).…”
Section: Tablementioning
confidence: 99%
See 1 more Smart Citation